Effects of aging upon the host response to implants. Issue 5 (14th February 2017) - Hachim, Daniel; Wang, Na; Lopresti, Samuel T.; Stahl, Elizabeth C.; Umeda, Yuta U.; Rege, Rahul D.; Carey, Sean T.; Mani, Deepa; Brown, Bryan N.
Abstract: Macrophage polarization during the host response is now a well‐accepted predictor of outcomes following material implantation. Immunosenescence, dysregulation of macrophage function, and delayed resolution of immune responses in aged individuals have all been demonstrated, suggesting that host responses to materials in aged individuals should differ from those in younger individuals. However, few studies examining the effects of aging upon the host response have been performed. The present work sought to elucidate the impacts of aging upon the host response to polypropylene mesh implanted into 8‐week‐old and 18‐month‐old mice. The results showed that there are significant differences in macrophage surface marker expression, migration, and polarization during the early host macrophage response and delayed resolution of the host response in 18‐month‐old versus 8‐week‐old mice. These differences could not be attributed to cell‐intrinsic defects alone, suggesting that the host macrophage response to implants is likely also dictated to a significant degree by the local tissue microenvironment. These results raise important questions about the design and testing of materials and devices often intended to treat aged individuals and suggest that an improved understanding of patient‐ and context‐dependent macrophage responses has the potential to improve outcomes in aged individuals. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 1281–1292, 2017.